Surgical Treatment of Carpal Tunnel Syndrome through a Minimal Incision on the Distal Wrist Crease: An Anatomical and Clinical Study - Yoo, Hye Mi; Lee, Kyoung Suk; Kim, Jun Sik; Kim, Nam Gyun (Archives of Plastic Surgery, 2015)
Background An anatomical analysis of the transverse carpal ligament (TCL) and the surrounding structures might help in identifying effective measures to minimize complications. Here, we present a surgical technique based on an anatomical study that was successfully applied in clinical settings.Methods Using 13 hands from 8 formalin-fixed cadavers, we measured the TCL length and thickness, correlation between the distal wrist crease and the proximal end of the TCL, and distance between the distal end of the TCL and the palmar arch; the TCL cross sections and the thickest parts were also examined. Clinically, fasciotomy was performed on the relevant parts of 15 hands from 13 patients by making a minimally invasive incision on the distal wrist crease. Postoperatively, a two-point discrimination check was conducted in which the sensations of the first, second, and third fingertips and the palmar cutaneous branch injuries were monitored (average duration, 7 months).Results In the 13 cadaveric hands, the distal wrist crease and the proximal end of the TCL were placed in the same location. The average length of the TCL and the distance from the distal TCL to the superficial palmar arch were 35.30±2.59 mm and 9.50±2.13 mm, respectively. The thickest part of the TCL was a region 25 mm distal to the distal wrist crease (average thickness, 4.00±0.57 mm). The 13 surgeries performed in the clinical settings yielded satisfactory results.Conclusions This peri-TCL anatomical study confirmed the safety of fasciotomy with a minimally invasive incision of the distal wrist crease. The clinical application of the technique indicated that the minimally invasive incision of the distal wrist crease was efficacious in the treatment of the carpal tunnel syndrome.
Keywords: Carpal tunnel syndrome; Median nerve; Anatomy; Wrist; Cadaver